Transducer like proteins of Campylobacter jejuni 81-176: role in chemotaxis and colonization of the chicken gastrointestinal tract - Chandrashekhar, Kshipra; Gangaiah, Dharanesh; Pina-Mimbela, Ruby; Kassem, Issmat I.; Jeon, Byeong H.; Rajashekara, Gireesh (Frontiers in Cellular and Infection Microbiology, 2015)
Transducer Like Proteins (Tlps), also known as Methyl accepting chemotaxis proteins (MCP), enable enteric pathogens to respond to changing nutrient levels in the environment by mediating taxis towards or away from specific chemoeffector molecules such as nutrients. Despite recent advances in the characterization of chemotaxis responses in Campylobacter jejuni, the impact of Tlps on the adaptation of this pathogen to disparate niches and hosts is not fully characterized. The latter is particularly evident in the case of C. jejuni 81-176, a strain that is known to be highly invasive. Furthermore, the cytoplasmic group C Tlps (Tlp5, 6, and 8) was not extensively evaluated. Here, we investigated the role of C. jejuni 81-176 Tlps in chemotaxis towards various substrates, biofilm formation, in vitro interaction with human intestinal cells, and chicken colonization. We found that the ∆tlp6 and ∆tlp10 mutants exhibited decreased chemotaxis towards aspartate whereas the ∆tlp6 mutant displayed a decreased chemotaxis towards Tri-Carboxylic Acid (TCA) cycle intermediates such as pyruvate, isocitrate, and succinate. Our findings also corroborated that more than one Tlp is involved in mediating chemotaxis towards the same nutrient. The deletion of tlps affected important phenotypes such as motility, biofilm formation, and invasion of human intestinal epithelial cells (INT-407). The ∆tlp8 mutant displayed increased motility in soft agar and showed decreased biofilm formation. The ∆tlp8 and ∆tlp9 mutants were significantly defective in invasion in INT-407 cells. The ∆tlp10 mutant was defective in colonization of the chicken proximal and distal gastrointestinal tract, while the ∆tlp6 and ∆tlp8 mutants showed reduced colonization of the duodenum and jejunum. Our results highlight the importance of Tlps in C. jejuni’s adaptation and pathobiology.